Dorsal Hand Vein Image Enhancement for Improve Recognition Rate Based on SIFT Keypoint Matching - Sathaporn Chanthamongkol; Boonchana Purahong; Attasit Lasakul (My University, 2013)
The quality of im automatic sys high recognize in this paper, by CLAHE(C that improve Gaussian and composed by for each image matching step the performa result shows t Gaussian and time matching
Keywords: Scale-invariant feature transform; E-commerce and Technology Innovations